Extensively Drug-Resistant Salmonella typhi XDR Infection at Rawalpindi Medical University and Allied Hospitals - Kausar Izhar, Kiran Ahmed, Maryyam Rehan, Muhammad Umar, Nadeem Ikram, Naeem Akhter, Kausar Izhar, Kiran Ahmed, Maryyam Rehan, Muhammad Umar, Nadeem Ikram, Naeem Akhter (Journal of Rawalpindi Medical College, 2020)
Objective: To evaluate the prevalence of extensively drug-resistant Salmonella typhi (XDR) in RMU Allied Hospitals. Study Design: A descriptive cross-sectional study. Material and Methods: It is a cross-sectional, prospective study conducted at RMU Allied Hospitals from January 2019–December 2019. Blood culture samples were received in the pathology lab, they were collected by simple random sampling and processed by conventional incubation. Antibiotic susceptibility of the isolates was done on Muller Hinton agar using modified Kirby Bauer disk diffusion method and antibiotic zone diameters were measured according to CLSI guidelines. Results: Out of the total 8045 cultures, 911 (11%) showed growth, among which 179 (20%) were Salmonella typhi and 135 (15%) XDR Salmonella. Meropenem revealed the highest sensitivity, Chloramphenicol, and Augmentin revealed the highest resistance. Conclusion: Blood culture results revealed Salmonella typhi 20% with a significant number of XDR Salmonella 15%. Antibiotics susceptibility pattern exhibits Meropenem and Azithromycin as the only antibiotics for XDR Salmonella. Salmonella typhi infection has a significantly high prevalence among children as compared to adults. (p=0.0017) Injudicious use of antibiotics is one of the important aspects of the occurrence of antibiotic-resistant Salmonella.